2012
DOI: 10.1208/s12248-012-9425-7
|View full text |Cite
|
Sign up to set email alerts
|

Determination of the Dominant Arachidonic Acid Cytochrome P450 Monooxygenases in Rat Heart, Lung, Kidney, and Liver: Protein Expression and Metabolite Kinetics

Abstract: Abstract. Cytochrome P450 (P450)-derived arachidonic acid (AA) metabolites serve pivotal physiological roles. Therefore, it is important to determine the dominant P450 AA monooxygenases in different organs. We investigated the P450 AA monooxygenases protein expression as well as regioselectivity, immunoinhibition, and kinetic profile of AA epoxygenation and hydroxylation in rat heart, lung, kidney, and liver. Thereafter, the predominant P450 epoxygenases and P450 hydroxylases in these organs were characterized… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
26
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 41 publications
(31 citation statements)
references
References 46 publications
5
26
0
Order By: Relevance
“…In line with the current findings, it has been reported that the expression of CYP2B1 and/or CYP2J3 was increased in SHR (Spontaneously hypertensive rat), pressure overload-induced cardiac hypertrophy, and isoproterenol-induced cardiac hypertrophy (Thum and Borlak, 2002;Althurwi et al, 2013;El-Sherbeni and El-Kadi, 2014). CYP2B1, CYP2C23, and CYP2J were all reported to produce EETs where CYP2C and CYP2J subfamilies appear to be the primary P450 epoxygenases, in rat and human heart, respectively (Roman, 2002;Imig, 2012;El-Sherbeni et al, 2013). EET levels are critically regulated by the sEH enzyme, as it catalyzes their degradation to DHETs, thus eliminating their biologic activity.…”
Section: P450s In the Development Of Cardiac Hypertrophysupporting
confidence: 89%
“…In line with the current findings, it has been reported that the expression of CYP2B1 and/or CYP2J3 was increased in SHR (Spontaneously hypertensive rat), pressure overload-induced cardiac hypertrophy, and isoproterenol-induced cardiac hypertrophy (Thum and Borlak, 2002;Althurwi et al, 2013;El-Sherbeni and El-Kadi, 2014). CYP2B1, CYP2C23, and CYP2J were all reported to produce EETs where CYP2C and CYP2J subfamilies appear to be the primary P450 epoxygenases, in rat and human heart, respectively (Roman, 2002;Imig, 2012;El-Sherbeni et al, 2013). EET levels are critically regulated by the sEH enzyme, as it catalyzes their degradation to DHETs, thus eliminating their biologic activity.…”
Section: P450s In the Development Of Cardiac Hypertrophysupporting
confidence: 89%
“…This is in line with our results that the liver has the highest formation rate of CYP1As major metabolites, v-1→4 HETEs, and the heart has the lowest rate. The expression of CYP2Cs has been reported to be the highest in the liver, followed by the kidneys, and it is lowest in the heart and lungs (El-Sherbeni et al, 2013). This finding correlates with the rate of EETs formation, which is highest in the liver, followed by kidneys, then the heart and lungs.…”
Section: Discussionmentioning
confidence: 94%
“…P450 expression and their catalytic activities are the two factors that dictate the contribution of a P450 enzyme to AA metabolism in a tissue. With respect to P450 dmd.aspetjournals.org expression, substantial differences have been reported between different tissues and organs (Zordoky et al, 2008;El-Sherbeni et al, 2013). Additionally, AA-metabolizing activity demonstrated great variation among P450 enzymes.…”
Section: Discussionmentioning
confidence: 99%
“…The results of this study found that 14,15-EEZE dose-dependently reversed the CP's To investigate why AA P450 enzyme metabolism was influenced by multiple doses of the CP, the expressions and catalyzing activities of AA-related P450 enzymes in the rat heart were studied. CYP2C11 and CYP2J3 are two main AA epoxygenases in the rat heart (El-Sherbeni et al, 2013). Cardiac CYP1A1, CYP2B1, and CYP2E1 have also been reported to display AA epoxygenase activity (El-Sherbeni and El-Kadi, 2014).…”
Section: Discussionmentioning
confidence: 99%